LQ45 Stock Index Abnormal Return Reaction to the Covid-19 Pandemic: the Even Study Methodology - Ikin Solihin; Sugiarto Sugiarto; Gracia Shinta S. Ugut; Edison Hulu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
LQ45 Index stocks are liquid stocks with high market capitalization, have a high trading frequency, growth prospects, and fairly good financial conditions, are not volatile and have been objectively selected by the IDX. This research aims to determine the abnormal return of LQ45 Stock Index to the covid-19 pandemic. This research uses even study method with population consisted entirely of daily data from the ten most populous cities in the United States. The result of this study shows that there are significant differences in abnormal returns before and after the announcement of the Covid-19 pandemic by WHO. The announcement of this pandemic is responded to as a negative signal by investors so that information regarding the announcement of the Covid-19 pandemic by the WHO is responded to early and at the time of launching the information no longer had any effect because the prices had moved towards equilibrium. The future research that extend the research time period and include other external factors such as lockdown policies or inflation is needed as the limitation in this research.